2020
DOI: 10.1002/advs.201903070
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Metal Chalcogenides for Boosting Water Splitting

Abstract: splitting (2H 2 O → 2H 2 + O 2 ), consisting of hydrogen evolution and oxygen evolution reaction (HER/OER), can convert electricity to chemical energy in H 2 and O 2 for further energy applications. The practical application of overall water splitting, however, is still limited due to the lack of effective and stable catalysts to reduce reaction energy barrier and enhance Faraday efficient for both reactions. [6][7][8][9][10] Different materials have been studied for overall water splitting catalysis, like met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
139
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 231 publications
(140 citation statements)
references
References 277 publications
(478 reference statements)
1
139
0
Order By: Relevance
“…[55,65,95] Despite the initial crystalline structure, it has been found that many catalysts go through surface reconstruction to form an amorphous structure, which is identified as the active site. [29,30] Different from the long-range order and translational symmetry for crystalline structure, the atoms arrangement in the amorphous structure is in disorder and thus provides some unique properties: 1) The inherent disorder can produce abundant irregular oriented bonds and defects as active sites to improve catalytic activity; [35,96] 2) The chemical fluctuations, local topology, and isotropic properties enable amorphous materials possess unique characteristics, i.e., elastic strain, magnetic properties, and corrosion resistance; [79,97] For example, Li and co-workers have successfully prepared a series of monometallic amorphous nanosheets (Ir NSs, Rh NSs, and Ru NSs), bimetal amorphous nanosheets (RhNi NSs, RhCo NSs, RhRu NSs, IrFe NSs, IrNi NSs, and IrCo NSs), and even trimetallic amorphous nanosheets (IrRhRu NSs) for improving the performance of OER in acidic environment. [97] A recent study has investigated the difference between the OER at amorphous structure and crystalline structure with RuTe 2 porous nanorods as model catalysts (Figure 6).…”
Section: Crystallinitymentioning
confidence: 99%
See 1 more Smart Citation
“…[55,65,95] Despite the initial crystalline structure, it has been found that many catalysts go through surface reconstruction to form an amorphous structure, which is identified as the active site. [29,30] Different from the long-range order and translational symmetry for crystalline structure, the atoms arrangement in the amorphous structure is in disorder and thus provides some unique properties: 1) The inherent disorder can produce abundant irregular oriented bonds and defects as active sites to improve catalytic activity; [35,96] 2) The chemical fluctuations, local topology, and isotropic properties enable amorphous materials possess unique characteristics, i.e., elastic strain, magnetic properties, and corrosion resistance; [79,97] For example, Li and co-workers have successfully prepared a series of monometallic amorphous nanosheets (Ir NSs, Rh NSs, and Ru NSs), bimetal amorphous nanosheets (RhNi NSs, RhCo NSs, RhRu NSs, IrFe NSs, IrNi NSs, and IrCo NSs), and even trimetallic amorphous nanosheets (IrRhRu NSs) for improving the performance of OER in acidic environment. [97] A recent study has investigated the difference between the OER at amorphous structure and crystalline structure with RuTe 2 porous nanorods as model catalysts (Figure 6).…”
Section: Crystallinitymentioning
confidence: 99%
“…Lattice strain caused by lattice vacancies, lattice distortion, or lattice mismatch can tune the electronic structure. [79] Lattice strain includes tensile strain and compressive strain, which, for example, under an octahedral coordination, favor the filling of in-plane (d x y 2 2…”
Section: Strainmentioning
confidence: 99%
“…15 Currently, transition metal-based chalcogenides, phosphides, oxides, and their derivatives are examined as bifunctional catalysts in an alkaline medium. 2,[16][17][18][19][20][21] However, these materials are still needed to be engineered to reduce the overpotentials in both anode and cathode during the electrochemical water splitting reactions. 22 It is expected that multicomponent transition metal-based catalysts can be an ideal candidate for electrocatalytic reactions due to their high redox states and improved conductivity over their single component ones.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] In this context, electrochemical water splitting, which converts electricity into storable hydrogen, is a viable and efficient solution to mitigate severe energy shortages and greenhouse gas emissions. [3] Among these strategies, hydrogen and oxygen evolution reactions, which occur on the cathode and anode, respectively, in a water electrolyzer, are considered as two critical half-reactions of the water-splitting process. [4] Theoretically, water splitting requires a thermodynamic Gibbs free energy (ΔG) of approximately 237.2 kJ mol −1 , corresponding to a standard potential (ΔE) of 1.23 V versus a reversible hydrogen electrode (RHE), which allows the thermodynamically uphill reaction to occur in the electrolyzer.…”
mentioning
confidence: 99%